DETERMINANTS OF CALCIUM INTAKE AMONG PREGNANT WOMEN IN RURAL AREAS OF EAST KUTAI REGENCY - Lia Agustin; Rismayanti M; Dian Rahmawati (Universitas STRADA Indonesia, 2026)
Inadequate calcium intake during pregnancy remains a major nutritional problem in rural areas and may increase the risk of adverse maternal and fetal outcomes. This study aimed to analyze the determinants of calcium intake among pregnant women in Sangkulirang, East Kutai Regency, Indonesia. A cross-sectional study was conducted among 52 pregnant women selected using purposive sampling. Calcium intake was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) and categorized based on Recommended Dietary Allowance (RDA). Data were analyzed using chi-square and logistic regression tests. Most respondents (61.5%) had inadequate calcium intake. Maternal knowledge (p=0.001), antenatal care utilization (p=0.003), occupation (p=0.041), education (p=0.045), and maternal age (p=0.041) were significantly associated with calcium intake. Maternal knowledge was identified as the dominant determinant (OR=5.21; 95% CI=1.89–14.32). Maternal knowledge and antenatal care utilization are important determinants of calcium intake among pregnant women in rural areas.